Características do trabalho e emprego da equipe de saúde da família: análise de indicadores de precarização - Lopes, Elizabete Silva de Jesus (2013)
The casualization of labor is one of the main problems associated with globalization and the restructuring of production processes in the capitalist system. Contributes to change the characteristics of the labor and employment in general, and particularly in the health sector. This study aimed to evaluate the characteristics of the labor and employment of the Family Health Program (PSF), focusing on indicators of precarious work in Feira de Santana, Bahia in 2012. This is an epidemiological cohort study cross- exploratory- descriptive, with a random sample stratified by geographic location, occupational category and level of assistance. Applied to 1,041 workers structured municipal public questionnaire. For the types of characteristics of vulnerable employment and working on the indicators of precariousness used the Grade of Membership (GoM) method - degree of belonging. 3 profiles were generated : profile " 1 " , characterized by less vulnerable workers , but with lower incomes; Profile " 2 " marked by workers in poorer working conditions and employment profile " 3 " less vulnerable workers , but with low social support . Findings reveal the existence of different vulnerabilities on indicators of precarious work among groups of workers PSF. Suggested to different actions for each group of workers in order to desprecarizar conditions of employment.